The new employee contract : how to find, keep, and elevate Gen Z talent - Onesto, Anthony (Apress, 2022)
Learn about Generation Z from the perspective of a manager at a company looking to recruit and retain staff. This book provides an in-depth analysis of who makes up Gen Z, what they want, and how businesses around the world can give that to them in a way that is meaningful. In the past, companies were not prepared for the generation of new talent called Millennials. Companies were surprised to learn that Millennials were different from those in Gen X and the Boomers. With the help of author Anthony Onesto, you will not be unprepared when working with those in Gen Z. The New Employee Contract dives into the needs and wants of this generation of talent that has been born on the iPhone and for whom gaming is second nature. Those in GenZ believe in loyalty and social goodness, use gaming mechanisms, and expect almost real-time delivery on their expectations. The patience of this generation is very short, which explains the success of platforms such as Snapchat and TikTok. All of this research is presented in a fun, compelling way in this book. Even if you are not working in management, you will want to understand these 74 million socially active Americans who hold $44 billion in direct buying power. What You Will Learn Understand what members of Gen Z want in a world of climate uncertainty, job losses, and automation Understand why automation is a worst case scenario for those in Gen Z Know how to give back a sense of control to those who belong to Gen Z Know what members of Gen Z are looking for, including quality of work vs. quantity of work Be aware of the way businesses need to develop this new contract with employees Who This Book Is For Chief executive officers, chief people officers/HR leaders/HR departments, and leaders/managers within companies. The book is also of use to venture capitalists, those handling private equity, and investors. A third audience includes college advisors, life coaches, and career coaches.